Pressure-Time Profile Analysis to Select Surfaces that Effectively Redistribute Pediatric Occipital Pressure. - Higer, Samantha. (2017)
Abstract: Pressure ulcers are a hospital-acquired condition with reported incidence of up to 27% in acutely ill infants and children, who are particularly vulnerable during long periods of immobilization. Pressure is a key risk factor for pressure ulcer formation and pressure-redistributing surfaces are used in the clinical setting to mitigate this risk. However, there is a lack of information on the most effective surfaces available to redistribute pressure in pediatric patients, especially because the occiput is the highest risk location for pediatric patients, while the sacrum and heels are at highest risk for adults. The aim of this research is to evaluate the pressure-redistributing properties of surfaces used to redistribute pressure under the bony prominence of the occiput of hospitalized pediatric patients through pressure mapping experiments on healthy children. A commercially available pressure mapping system is validated for use in the pediatric population through studies on sensitivity, accuracy, creep and repeatability. Then, the capacitive pressure sensor is used to measure mean peak pressure and contact area between the occipital region of the skull of children under 6 years old and each of four pressure-redistributing surfaces: gel, foam, fluidized, and air cushion. Lastly, finite element analysis is performed to simulate the pressure generated on the occiput during contact with a foam surface for two loading conditions. Predictions from the finite element model are compared to experimental pressure mapping data. The results of this study provide clinical recommendations for pediatric pressure ulcer prevention protocols.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Thomas James.; Committee: Daniel Hannon, Gary Leisk, and Donald Lombardi.; Keywords: Mechanical engineering, Medicine, and Health sciences.